Resources and Energy Management: the case of the Agropoli Urban Plan - Moccia, Francesco Domenico (TeMA - Journal of Land Use, Mobility and Environment, 2013)
The theme of the resources management, of the energy-environment retrofitting framed in strategies to mitigate and adapt to climate change, aimed at energy saving, energy generating from alternative sources, metabolism and natural resources is one of the central topics the City Urban Planning of the City of Agropoli, currently approved by Resolution of the City Council no. 110 of 18.04.2013.The plan is part of the wider system of actions taken by the Municipality to achieve the objectives on the environment posed by the European Union with the Directive " EP seals climate change package 20-20-20". In particular the planning tool provides a series of actions aimed at containing the uses energy through measures to rationalize, do not waste and reduce the use of non-renewable resources, by promoting "best practices" from the management of public assets, the use of innovative technologies in all sectors and activities; the diffusion of renewable energy production, with care to avoid impacts and interference with the historical landscape, including the promotion of programs and interventions of public management. The different strategic projects will take care of specific actions also for the experimental use of innovative technologies.The article proposes, within the framework of strategies and actions at the European level for small municipalities, the example of the City of Agropoli drawing conclusions and reflections on the theme of energy saving relative to the housing stock.